DIGITAL PSYCHOLOGICAL SUPPORT FOR THE ADAPTATION OF YOUNG PRESCHOOL CHILDREN TO PRESCHOOL EDUCATIONAL INSTITUTIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the psychological support of young preschool children during their adaptation to preschool educational institutions in the context of the digital world. The paper focuses on emotional security, separation anxiety, social communication, teacher-child interaction and the role of family participation in the adaptation period. Particular attention is given to the pedagogically justified use of digital tools: parent-teacher communication platforms, digital adaptation diaries, short visual routines, emotion cards and developmental games that do not replace direct human contact but help adults observe, understand and support the child more accurately. The study is based on theoretical analysis, observation, interviews with educators and parents, and comparative interpretation of adaptation indicators. The results show that the combination of a safe psychological environment, play-based interaction and careful digital monitoring can reduce emotional tension, improve communication with peers and strengthen children’s positive attitude toward preschool education. The article argues that digital psychological support must be age-appropriate, ethically organized and subordinated to the child’s emotional well-being.